Malaria in African schoolchildren: options for control. - Brooker, S; Clarke, S; Snow, R; Bundy, D (2008)
Intensified malaria control efforts among young African children may increase disease risks among older children who attend school and whose education may be impaired by malaria. However, there is currently no consensus as to the approach to malaria control in schools, with relevant intervention strategies varying according to patterns of malaria transmission. Life skills messages regarding prevention and accessing prompt treatment are important everywhere. Providing free bed nets to schoolchildren may bring individual and community benefits and should be widely promoted. New approaches to school-based chemoprevention and treatment may also be able to play an important role in school-based malaria control, although these require further investigation.